Neurodynamics analysis of cochlear hair cell activity - Weifeng Rong (Theoretical and Applied Mechanics Letters, 2020)
There have been many studies on the effect of cochlea basal membrane movement on the resolution of different frequencies and intensities. However, these studies did not take into account the influence of power and energy consumption of the hair cells in the process of the electromotility movement, as well as the neurodynamic mechanism that produced this effect. This makes previous studies unable to fully clarify the function of outer hair cells (OHCs) and the mechanism of sound amplification. To this end, we introduce the gate conductance characteristics of the hair cells in the mechanical process of increasing frequency selectivity. The research finds that the low attenuation of OHCs membrane potential and the high gain in OHC power and energy consumption caused that OHC amplification is driven by electromotility. The research results show that the amplification of the OHCs is driven by low attenuation of membrane potential and high gain of power and energy consumption. This conclusion profoundly reveals the physiological mechanism of the electromotility movement. Keywords: Hair cells, Sound frequencies, Membrane potential, Power, Outer hair cell amplification